Pengaruh Penggunaan Mulsa terhadap Pertumbuhan dan Hasil Tanaman Sawi (Brassica juncea L.) pada Jarak Tanam yang Berbeda - Baso Amir (Savana Cendana, 2018)
The decline in crop productivity can be caused by environmental factors. Lack of water availability, nutrients, light gain and competition between plants at denser plant spacing and competition for plants with weeds can lead to a less optimal growth of crops, which results in less production. This study aims to determine the effect of mulch use with several different spacing on the growth and yield of mustard plants. The study was conducted using Factorial Complete Group Random Design (RCBD) which was repeated 4 (four) times. The first factor is the type of mulch consisting of three levels, namely M0: without mulch, M1: black silver plastic mulch, M2: straw mulch. The second factor is the spacing which consists of three levels, namely JT1: 20x25 cm, JT2: 30x25 cm, JT3: 40x25 cm. Observation parameters consisted of plant height, number of leaves, leaf area, root length, and plant fresh weight. Data analysis was performed using SAS software with variant analysis (Anova) at the level of 5%. If the results of variance analysis show a significant difference between treatments, the analysis is continued by Duncan's multiple distance test (DMRT). The results showed that the provision of straw mulch with the spacing of 30x25 cm between plants showed a better effect with a higher value, namely the number of leaves 13.50 strands, leaf area 63.13 cm2, root length 8.18 cm and fresh plant weights of 210.00 grams/plant compared to other treatment.